(3GdJYOj cCSGS Y`Ge ddeSFhdjI GdJbUjQjI (B: s (3OQGSI ebGQfI aj GdTQjYI GdESdGejI hGdbGfhf GdEfLdjRj (B/ s - (3EjfGS aQL GdYGRejs; (3eMehO HdGd egQGfs; (3eMehO YHO GdQMef eMeOs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2014)
(3Ef GdJYOj gh TQW gGe ddeSFhdjI GdJbUjQjI aj GdTQjYI GdESdGejI h GdbGfhf GdEfLdjRj dcfg dG jeKd CSGSB YGeB ddeSFhdjI GdJbUjQjI ajgeG (B: (3EP dG jTJQW JhGaQ TQW GdJYOj aj GdeHGTQI h GdJSHH aj GdTQjYI (B. (3CeG GdJSHH aEf GdbGYOI GdYGeI gh GTJQGW JhGaQ GdJYOj aj GdJSHH dUdGMjJg ceUOQ ddeSFhdjI GdJbUjQjI (B: (3h eY Pdc jecf Cf jUdM GdJSHH ceUOQ ddeSFhdjI GdJbUjQjI h dh de jbJQf Hg TQW GdJYOj h Pdc EPG JhGaQ aj GdJSHH GdeYfi GdeYJHQ TQYB h gh chfg eeG jaVj ZGdHB h HMSH GdYGOI Edi hbhY GdVQQ HGdZjQ (B. (3CeG GdbGfhf GdEfLdjRj (B: (3aEfg dG jTJQW JhGaQ TQW GdJYOj aj LejY GdCaYGd GdehLHI ddeSFhdjI GdJbUjQjI (B: (3aGdJYOi jLH JhGaQg ai HYVgG cCaYGd GdeSGS h aYd GdEgeGd h eSFhdjI UGMH GdecGf h aYd GdbVjI GdcjOjI h GdeSFhdjI Yf GdeQV GdfaSi(B: (3HjfeG dG jTJQW JhGaQ GdJYOi ai CaYGd CNQi caYd GdeVGjbI GdYGeI h GdeSFhdjI HfGA Ydi bGYOI QjdGfOR h adJTQ(B.s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2014.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B567-579.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3CKGQ GdeSDhdjI GdJbUjQjIs; (3GdTQjYI GdESdGejIs; (3GdJYOjs; (3GdbGfhf GdeOfj GdEfLdjRjs; (3bGYOI QjdGfOR hadJTQs; (3GdeSGSs; (3GdbVjI GdcjOjIs; (3GdeSFhdjI Yf GdeQV GdfaSjs; (3GdJYOj aj GdEaRGYs; (3GdeVGjbI GdYGeIs; (3GdeSFhdjI GdJbUjQjIs; (3GdJYOj aj GdJSHHs; (3hGLH GdYfGjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs